Household Waste Management As a Medium for Maggot Cultivation in Resun villages - Afrillia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service program was carried out in Resun Village, North Lingga District, Lingga Regency. The waste problem in Resun Village, North Lingga District, Lingga Regency, has been a problem that has been born for a long time and has not received maximum treatment due to the lack of facilities and infrastructure. This internship activity resulted in a program after observations for some time, namely socialization about waste management, a waste sorting program from home, and also a maggot cultivation program with the use of organic waste as a feed medium. The purpose of the socialization of this maggot cultivation program is to provide solutions to reduce waste accumulation and make waste more useful. Socialization of the maggot (Hermetia illucens) cultivation program to the community in Resun Village, North Lingga District, Lingga Regency, Riau Islands Province.